MEDIAMORFOSIS DAN PERSAINGAN MEDIA - Syafiie, Sri Syamsiah Lestari (Universitas Semarang, 2010)
It s predicted when there is a new media, the older will die. Infact, that is not proved. The old media still exist. Mediamorfosis is the key. Media change to survive and compete with other. Exacly, It must be suppot by human resourses and campus must be the center of it.